Subverting the Dominant Order: Narrative as Weapon in Simone de Beauvoir's Tous les hommes sont mortels - Barbara Klaw (Studies in 20th & 21st Century Literature, 1996)
This essay argues that through the narrative techniques of point of view and embedding, Beauvoir carefully constructed her narrative and those of her male and female characters in Tous les hommes sont mortels, her third novel, published in 1946, in order to explain why males dominate society and to encourage women to fight against the current patriarchal social order. Many critics view Fosca as the principal character, and his 400-page embedded recapitulation of his past as the predominant text, but shifting the focus from Fosca to Régine, who constitutes the only focalizer of present events in the embedding text, clarifies many details previously judged as faults. This study advances that the awkwardness of the characters and of the linking of the narrative strands needs to be reinterpreted in relation to thematic repetitions and contradictions, the narrator's reliability, the use of time, psychoanalytic theory, the author's life at the time of writing, cultural history, and theories concerning énonciation. The interplay of these elements indicates the ways in which narrative is wielded as a weapon which ultimately promotes female independence in the struggle between the sexes.
Keywords: narrative; Simone de Beauvoir; Tous les hommes sont mortels; males; females; society; gender; patriarchy; énonciation; female independence